Organizational atmosphere and management control in a training center for the sugar industry - Villa González del Pino, Eulalia M.; Pons Murguía, Ramón A.; Martínez Martínez, Carlos Cristóbal; Castellanos Castillo, José R. (Centro Azúcar Journal, 2006)
This work is aimed to measure the organizational atmosphere in a Training Center for the Sugar Industry that is implementing a change process towards a new management system process- oriented to achieve organizational excellence and quality of its management results. Study was made in 122 professionals and employees. It was a transversal study design, analytical and descriptive, made from a confidential questionnaire. The statistical analysis included a basic statistical study and a factor analysis of principal components. There are three factors that define the organizational atmosphere with a representativity of 82, 3%. As a main conclusion of research work it was considered the immediate introduction of modifications in style and management methods as well as in workers´ attitude, in correspondence with the organizational strategy and its management system.